PEMBERIAN PUPUK KOTORAN AYAM DAN CANGKANG TELUR UNTUK MENINGKATKAN KETERSEDIAAN HARA N, P, K DAN PERTUMBUHAN TANAMAN KEDELAI PADA ULTISOLS - Juraidah, Juraidah; Hayati, Rita; Vitri Indrawati, Urai Suci Yulies (Fakultas Pertanian, Universitas Janabadra, 2024)
Cultivation of soybean plants in Ultisols is faced with problems of acidity and high Al content, as well as low fertility in both macro and micronutrients. This research aims to determine the effect of the interaction of chicken manure and egg shells on the availability of N, P, and K nutrients and the growth of soybean plants. The research was conducted from January to May 2022 at the Experimental Garden, Faculty of Agriculture, Tanjungpura University. A Randomized Block Design (RAK) with two factors, namely chicken manure (0, 50, 75, and 100 tons/ha) and egg shells (0, 1, 2, and 3 tons/ha) was used in this experiment. The research results showed that the interaction of providing chicken manure (100 tons/ha) and egg shells (3 tons/ha) could increase N nutrient availability by 86.66%. Providing 50 tons/ha of chicken manure can increase soil pH and P and K nutrient availability by 4.01%, 286.66%, and 95.29% respectively. The growth parameters of plant height, stem diameter, and number of leaves increased by 91.48%, 120.83%, and 221.27%, respectively. Providing 1 ton/ha of eggshells can increase soil pH by 2.48%. These results confirm that the application of chicken manure and egg shells can increase the availability of soil nutrients and increase the growth of soybean plants in Ultisols.